The Islamic Perspective on Managing Youth Wealth in Sharia Finance - Bte Badrul Munir, Maryam; Badrul Munir, Tahani (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study examines the Islamic perspective on the financial management of youth via the lens of maqasid syariah, encompassing five principal objectives: orientasi ibadah (worship orientation), orientasi jiwa (spiritual orientation), orientasi akal (mindful orientation), orientasi keturunan (offspring orientation), dan orientasi harta (property orientation). The research seeks to provide a financial management framework for youth, grounded in Syariah principles and an ibadah-focused perspective that regards wealth stewardship as an aspect of devotion to Allah. A qualitative methodology was utilized, incorporating comprehensive interviews with Islamic finance scholars, young practitioners, and community leaders, alongside document analysis of both ancient and contemporary Islamic economic literature. The results indicate that proficient youth money management is not solely transactional but transformative—cultivating spiritual discipline (ibadah), psychological equilibrium (nafs), intellectual development (‘aql), familial duty (nasl), and sustainable financial practices (mal). The study reveals a deficiency in contemporary financial education for Muslim adolescents, frequently devoid of Syariah value integration. This research underscores the significance of early financial education that internalizes maqasid-oriented principles, resulting in more responsible, ethical, and influential financial actions. The proposed approach aids in the formulation of policies for Islamic financial literacy programs and bolsters youth empowerment initiatives by synchronizing financial behaviors with enduring spiritual and societal welfare